Forming Students’ Character through School Culture in Senior High School Taruna Nusantara Magelang - Kurniawati, Eni Kurniawati; Sunarso, Sunarso (SCAD Independent, 2019)
Abstract Policy on character education has long been applied in Indonesia, with the hope to develop a civilization to be more dignified and become savvy citizens and not experiencing a moral crisis. However, by looking at the reality of the matter at this time, a moral crisis never stops destroying the nation's generation. If not treated immediately it will trigger the development of characters that do not reflect the identity and character of the nation that will result in a weak future generation. Therefore, this study aims to determine the character of the students that is implanted or formed through the school culture in Taruna Nusantara. The research is a qualitative case study research, the data collection techniques used were interviews, observation and documentation. The results showed that the effective character education is the transformation of culture and life in a boarding school that is in Taruna Nusantara High School in Magelang. Character formation of students can be achieved through school's culture as being in the grand of designing character education, because of character as a